Toponyms and Narratives in Samut Songkhram Province - Tawichai, Suphachai; Wutthichamnong, Weena (Journal of Arts and Thai Studies, 2024)
Objectives: This article aimed at investigating meanings and origins of toponyms (village names) and analyzing the contents of narratives of the place names in Samut Songkhram Province. Methods: Semantic fields was used to investigate meanings and origins of village names, while conventional content analysis was adopted to analyze the contents of narratives of the place names in Samut Songkhram Province. Results: The findings revealed that there were 14 types of the meanings of the village names: 1) water and water resources, 2) place of construction, 3) location of the place, 4) human beings, 5) geography, 6) occupations and lifestyle, 7) flora, 8) numbers, 9) nature, 10) manners and action, 11) deities and auspicious things, 12) foods, 13) animals, and 14) others. Interestingly, the village names are related to socio-cultural contexts and the geography of the area. For the narratives of the place names, 11 issues were found in the contents which can be categorized into four groups: 1) narratives related to historical events, 2) narratives related to lifestyle of the communities in the past, 3) narratives related to nature of the places, and 4) narratives related to the belief system of the communities. Application of this study: The findings indicated that village names and their narratives can serve as resources which can be applied to create value for the well-being of local people in the community and develop sustainable tourism in Samut Songkhram Province.